Rising public costs of preterm infant hospitalization in South Korea from a nationwide observational study - Ji Young Lee; Joonsik Park; Myeongjee Lee; Minkyung Han; Sung Min Lim; Jee Yeon Baek; Ji-Man Kang; Min Soo Park; Inkyung Jung; Jong Gyun Ahn (Scientific Reports)
Abstract Despite the decline in the overall birth rate, increasing preterm births and associated medical costs pose a national concern. We analyze hospitalization costs covered by national public insurance for preterm infants. Population-based data, obtained from the National Health Insurance Service (NHIS), which is operated by the Health Insurance Review and Assessment Service, were used for the study. Preterm births from January 1, 2008 to December 31, 2020 were included, using International Classification of Diseases and Related Health Problems, 10th edition (P07.2, extremely preterm < 28 weeks gestational age, P07.3, non-extremely preterm). The primary outcomes related to cost from the first hospitalization due to preterm births and medication, and laboratory, radiological, and functional tests by gestational age and birth weight. Additionally, we assessed the readmission rates of preterm infants and the associated medical costs. A total of 5,312,886 live infants were born, of which 90,575 were claimed as preterm birth hospitalization. The total medical cost per patient increased almost three-fold from $7,390.90 to $20,209.59 from 2008 to 2020; for the extremely preterm group, it increased four-fold ($13,961.03 to $55,984.47). The readmission rate within 90 days of discharge was 62.5%; however, a greater proportion of the extremely preterm, as compared to the non-extremely preterm (16.1% vs. 8.32%, P < 0.001) group was readmitted within 30 days. The extremely preterm group also incurred higher costs associated with readmission (mean $4293.8 vs. $2975.4, P < 0.001). This study reveals not only the increase in preterm birth rate in South Korea, but also in the associated medical costs. Further attention should be paid to efficient resource allocation at the national level to relieve the medical burden of preterm births.